Al2O3 Nanoparticles Promote the Removal of Carbamazepine in Water by Chlorella vulgaris Immobilized in Sodium Alginate Gel Beads - Wu Yi-cheng; Yang Ai-li; Gao Wei; Fu Hai-yan; Wang Ze-jie (Journal of Chemistry)
The roles of Al2O3 nanoparticles on the removal of carbamazepine (CBZ) by Chlorella vulgaris immobilized in sodium alginate gel beads were for the first time investigated. The optimum conditions to prepare immobilized C. vulgaris beads with addition of Al2O3 nanoparticles were determined as follows: C. vulgaris density was 3.0 × 106 cells for 1 mL sodium alginate solution, Al2O3 nanoparticle concentration was 0.5 g/L, and concentrations of sodium alginate and CaCl2 were 1.6% and 1%, respectively. The results showed that the proposed algae beads achieved the highest CBZ removal rate of 89.6% after 4 days of treatment, relative to 68.84%, 48.56%, and 17.76% in sodium alginate-immobilized C. vulgaris, free microalgae, and Al2O3 nanoparticle alginate beads, respectively. The results also showed that the CBZ removal rate increased with more proposed algae beads, while decreased with increased bead diameter. The algae beads exhibited excellent CBZ removal ability even after three recycles. This work provided an economical and effective approach to remove CBZ from water.